CARBOHYDRATE METABOLISM IN BLOOD DONORS - Iroda Nozimjon Qizi, Sokhibova (Journal of Medical Genetics and Clinical Biology, 2024)
Objective: This study investigates the effects of blood donation on carbohydrate metabolism and examines dietary strategies to support donor health. Blood donation is vital for healthcare but can temporarily disrupt glucose levels, potentially causing symptoms like fatigue and dizziness, particularly in donors susceptible to blood sugar fluctuations. Method: The research integrates a review of WHO guidelines, an analysis of recent studies on carbohydrate metabolism in blood donors, and the development of specific nutritional recommendations to support recovery. The WHO guidelines offer foundational insights into safe donation practices, while scientific research provides data on glucose regulation and recovery needs. Results: Findings reveal that complex carbohydrates before donation stabilize glucose levels, while fast-absorbing carbohydrates after donation rapidly restore energy, reducing symptoms associated with blood sugar dips. Regular donation may also benefit individuals with high carbohydrate intake by regulating glucose levels and reducing disease risks. Novelty: This study uniquely combines WHO recommendations with recent scientific insights to provide a practical, evidence-based dietary framework specifically tailored for blood donors, addressing both donor safety and physiological recovery. This approach emphasizes the importance of carbohydrate type and timing, offering a nuanced perspective for dietary management in donation contexts, and underscores the need for future research on personalized nutrition strategies for optimal donor health.